PEMBERDAYAAN MASYARAKAT DAERAH WISATA GILI TRAWANGAN LOMBOK BERBASIS CAEC (COMMUNITY OF ACTIVE ENGLISH COMMUNICATION) - Jumadil, Jumadil; Muliadi, Agus (Lumbung Inovasi: Jurnal Pengabdian kepada Masyarakat, 2016)
Gili Trawangan is rich in beaches and tourist spots underwater charming. Means oftransport in GiliTrawangan is cidomo, speedboat and bike. Smoothness and comfort traveled in dyke is strongly influenced by the quality of service of the coachman cidomo, speedboat driver and guide. Therefore, the necessary training and coaching programs for people of foreign languages in GiliTrawangan tour players. KKN PPM program is conducted in stages: (1) Selection of ParticipantsÂ KKN PPM students; (2) The debriefing student participants KKN PPM; (3) The survey location; (4) Socialization KKN PPM program; (5) debriefing tour players; (6) Training and mentoring 2 times a week for 3 months.Training and mentoring, held as many as 25 meetings. At the beginning of training, team training intensifies Vocabulary and selanjutkan team tenses material intensify and Speaking. Results of the assessment showed significant improvement appointment: (1) On Vocabulary capability, as many as 3 people categorized as Very Good, 25 Good category, 2 category Not Good. (2) In tenses capability, as many as 26 people categorized as Good, 4 categorized Less Good. (3) In speaking ability, as many as four people categorized as Very Good, 25 people categorized as Good, 1 Good Less category.